Tìm M đề B chia hết cho C
B=x^3-4x^2+4x-m
giúp mik vs mik cần gấp
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(m^2+n^2-5\right)^2-4\left(mn+2\right)^2\)
\(=\left(m^2+n^2-5\right)^2-\left(2mn+4\right)^2\)
\(=\left(m^2+n^2-5-2mn-4\right)\left(m^2+n^2-5+2mn+4\right)\)
\(=\left[\left(m^2-2mn+n^2\right)-3^2\right].\left[\left(m^2+2mn+n^2\right)-1^2\right]\)
\(=\left[\left(m-n\right)^2-3^2\right]\left[\left(m+n\right)^2-1^2\right]\)
\(=\left(m-n-3\right)\left(m-n+3\right)\left(m+n-1\right)\left(m+n+1\right)\)
\(\left(a-2\right)\left(a+2\right)\left(a^2+4\right)-\left(a^2+5\right)\left(a^2-5\right)\)
\(=\left(a^2-4\right)\left(a^2+4\right)-\left(a^2+5\right)\left(a^2-5\right)\)
\(=a^4-16-a^4+25\)
\(=9\)
x2 - 5x = 0
=> x(x - 5) = 0
=> \(\orbr{\begin{cases}x=0\\x-5=0\end{cases}}\)
=> \(\orbr{\begin{cases}x=0\\x=5\end{cases}}\)
b) (3x - 5)2 - 4 = 0
=> (3x - 5)2 = 0 + 4
=> (3x - 5)2 = 4
=> (3x - 5)2 = 22
=> \(\orbr{\begin{cases}3x-5=2\\3x-5=-2\end{cases}}\)
=> \(\orbr{\begin{cases}3x=7\\3x=3\end{cases}}\)
=> \(\orbr{\begin{cases}x=\frac{7}{3}\\x=1\end{cases}}\)